Efficacy and Tolerability of a New Facial 2-Mercaptonicotinoyl Glycine-Containing Depigmenting Serum Versus Hydroquinone 4% over 3-Month Treatment of Facial Melasma - Thierry Passeron; Delphine Kerob; Guénaëlle Le Dantec; Anne-Laure Demessant-Flavigny; Alessandro R. do Nascimento; Renato Moura; Samir Salah; Mariana Feiges; Erika Fernandez; Andrew Alexis (Dermatology and Therapy)
Abstract Introduction Topical treatment with hydroquinone 4% and hydroquinone-based preparations is the gold standard of care for melasma; however, it is limited by complications. 2-Mercaptonicotinoyl glycine (Melasyl™) is a new active ingredient targeting melanin synthesis without impairing the tyrosinase enzyme, with proven efficacy and safety. This study assessed the non-inferiority of a new facial depigmenting serum Mela B3® (MB3), containing 0.5% 2-mercaptonicotinoyl glycine, versus hydroquinone 4%. Methods This comparative, non-inferiority, randomized, investigator-blind, parallel-group investigation included adult women with mild-to-severe epidermal or mixed facial melasma. Patients received 3-month treatment with MB3 (twice daily) or hydroquinone 4% (once daily) and applied a broad spectrum SPF 50+/UVA tinted sunscreen (twice daily). Evaluations were conducted at day (D) 0, D28, D56, and D84 of treatment by a dermatologist and the patients. Non-inferiority analysis was performed at D84 on the Modified Melasma Area and Severity Index (mMASI) (non-inferiority margin 1.3). Efficacy assessments included mMASI, Melasma Quality of Life questionnaire (MELASQoL), and Patient Unique Stigmatization Holistic tool in Dermatology (PUSH-D) scores at each visit. Safety and tolerance were evaluated. Results The study included 109 women (phototypes I–IV; > 80% had phototypes III–IV). At D84, the estimated difference in mMASI score between MB3 and hydroquinone 4% was 0.46 (95% confidence interval − 0.25–1.17). Both groups demonstrated statistically significant improvements on mMASI from D28 versus baseline. The MELASQoL and PUSH-D scores decreased significantly from D28 in both groups (no difference between the groups). Nevertheless, a significant difference in the PUSH-D score was observed at D28 and D56 in favor of MB3. MB3 showed better tolerability versus hydroquinone 4% at D28 with fewer local skin reactions (6.0% versus 21.4%, respectively; p = 0.0286). Conclusion MB3 shows non-inferior efficacy and better tolerability compared with hydroquinone 4%. MB3 is an effective and well-tolerated alternative option for the topical treatment of melasma. Clinical Trial Registration NCT06787846.